Pendidikan Keluarga Perspektif Al-Qur’an - Mohammad ruslan (El-Furqania : Jurnal Ushuluddin dan Ilmu-Ilmu Keislaman, 2020)
Education is an important requirement for every country in general and schools in particular. What's more is religious education, where parents play an important role in education Early. Thus the first form of education is present in family life. Education is nothing but emphasizing the concept of Islamic education which makes the problem of servitude to God and obedience to Him the axis of all life. It should also be noted that children's physical education is an inseparable part of mental, mental, and personal education. The task of parents in educating children from childhood will introduce children to the existence of their god, who makes and manages the universe, understands who the prophet is, and understands their religion, so that they understand and understand the duty to live in this world is to worship God alone with following the sunnah of His Messenger. It is clear, that Islam teaches them to carry out their children's education, which is based on the view that children as creatures who are growing and developing towards maturity, have basic skills that are dynamic and responsive to external influences and themselves. Keywords: education, family, Al-Qur'an.